The Effect of Doping by Sr on the Structural, Mechanical and Electrical Characterization of La1Ba1-xSrx Ca2Cu4O8.5+Î´ - Jasim, Kareem A.; Thejeel, Mohammed A.N.; Al-Khafaji, Raghad Subhi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Sr doped La1Ba1-xSrx Ca2Cu4O8.5+Î´ samples with 0 â‰¤ x â‰¤ 0.3 had been prepared using the solid state reaction. The samples were claimed at 800Â°C for 3hr, palletized and sintered at 860Â°C for 20hr in air . Dielectric constant and loss by means of capacitance have been investigated with frequencies in the range of 1kHZ to 1MHZ for our samples at room temperature. Also, Shore hardness has been measured. The dielectric constant and loss decrease slightly with the increase of frequency for all compounds. Additionally, the partial substitution of Sr+2 into Ba+2 sites never have effect on the dielectric properties. X-ray diffraction (XRD) analysis showed a tetragonal structure and the as grown La1Ba1-xSrx Ca2Cu4O8.5+Î´  correspond to the 1124 phase. It was found that the change of the Sr concentrations of all our samples produces a change in a, c and c/a parameters.